Selecting Rural Development Paths Based on Village Multifunction: A Case of Jingjiang City, China - Tianqi He; Weifeng Qiao; Kaiyang Jia; Yibei Chai; Yi Hu; Pan Sun; Yahua Wang; Ting Feng (Complexity)
The diverse value of rural areas has been gradually highlighted, and promoting the sustainable development of rural areas with the theoretical guidance of rural multifunction is the key to realizing rural revitalization. This study defined the concept of rural multifunction from the perspective of resident’s demands and divided it into five main functions including rural agricultural production, nonagricultural production, living, ecological environment, and social security. By constructing the evaluation index system of rural multifunction, we analysed the spatial distribution characteristics of 160 villages of Jingjiang in Jiangsu Province. And functional combinations were identified to select targeted rural development paths oriented by balanced development of rural multifunction. The results showed the following. (1) The development of various rural functions in Jingjiang city was uneven, and agricultural production function still dominated. (2) The villages with strong agricultural production function were mainly concentrated in the northwest, while the villages with a high level of nonagricultural production function were mostly distributed in the industrial parks or around towns. There is still much room for improvement in social security function, especially in areas dominated by nonagricultural production. Nonagricultural production function had a negative effect on the ecological environment function, which is contrary to the agricultural production function. (3) Balanced development rather than equal development of rural functions should be pursued to achieve multifunctionality. Scientific guidance for the functional growth of villages in Jingjiang city and theoretical support for the microscale evaluation of rural multifunction and its application were provided by the research results.